Unraveling the Mystery of Cold Stress-Induced Myocardial Injury - Kong, Xue; Liu, Haitao; He, Xiaole; Sun, Yang; Ge, Wei (Frontiers in Physiology, 2020)
Exposure to low ambient temperature can cause great challenge to human body health, epidemiology investigation shows that many countries in the cold winter both in emergency admission rate and mortality rate was increased, especially associated with the adverse events of cardiovascular system, the cold has become one of the important risk factors of cardiovascular death. Through the method of echocardiography and myocardial histology, many clinical and animal experiments have observed that cold stress can cause a variety of pathological and pathophysiological injuries, including ventricular wall thickening, cardiac hypertrophy, elevated blood pressure, decreased cardiac function, and myocardial interstitial fibrosis. In order to clarify the potential mechanism, further study through biochemical and molecular biology experiments show that cold stress triggered mitochondrial injury, intracellular Ca2 + properties changes, generation of reactive oxygen species(ROS) and other superoxide, regulate the gene expression and protein levels of apoptosis and autophagy, as well as up regulation of related enzyme activity and enhance the sensitivity of adrenergic receptor etc.. These findings suggest that cold stress may damage myocardium through mitochondrial injury, apoptosis, autophagy, metabolism, oxidative stress and neuroendocrine pathways. Although the exact pathway has not been fully understood, it has been found that endothelin(ET-A) receptor, endoplasmic reticulum(ER) stress, TRPV1, mitochondrial related protein including NRFs and UCP-2, ROS, Nrf2-Keap1 signaling pathway, Bcl-2/Bax pathway and lipoprotein lipase (LPL) may play an pivotal role. The current research shows that cold stress lead to myocardial injury is caused by multiple pathways involving multiple signaling molecules. For myocardial injury caused by cold stress, more comprehensive and in-depth mechanisms and exact pathways need more basic experiments to further explore.